Characterization and butanol/ethanol sensing properties of mixed tungsten oxide and copper tungstate films obtained by spray-sol-gel - Damián M.A. (2003)
This work has been financially supported by the International Program for Physical Science of Uppsala University (IPPS), the Instituto de Investigación of Universidad Nacional de Ingenieria, and CONCYTEC (Peruvian Research Council).